2019
DOI: 10.1002/ardp.201900029
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, biological evaluation, and molecular modeling studies of rhodanine derivatives as pancreatic lipase inhibitors

Abstract: A series of rhodanine‐3‐acetic acid derivatives were synthesized via Knoevenagel condensation of rhodanine‐3‐acetic acid with various substituted aromatic aldehydes. The synthesized derivatives were screened in vitro for understanding the inhibitory potential towards pancreatic lipase (PL), a key enzyme responsible for the digestion of dietary fats. Derivative 8f exhibited a potential inhibitory activity towards PL (IC50 = 5.16 µM), comparable to that of the standard drug, orlistat (0.99 µM). An increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Natural plant-derived compounds (alkaloids, saponins, carotenoids, glycosides, polyphenols, polysaccharides, and terpenoids) and microorganism-derived compounds (lipstatin, valilactone, and panclicins) have been isolated and reported to inhibit in vitro and in vivo pancreatic lipase [ 16 , 17 , 18 ]. Synthetic compounds with diverse structures have been prepared and screened for pancreatic lipase inhibitory activity [ 19 , 20 , 21 , 22 ]. Along with the conventional approaches, in silico models such as 3D QSAR, 2D pharmacophore, molecular docking, and molecular dynamics simulations are utilized to identify potential bioactive compounds for obesity treatment [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural plant-derived compounds (alkaloids, saponins, carotenoids, glycosides, polyphenols, polysaccharides, and terpenoids) and microorganism-derived compounds (lipstatin, valilactone, and panclicins) have been isolated and reported to inhibit in vitro and in vivo pancreatic lipase [ 16 , 17 , 18 ]. Synthetic compounds with diverse structures have been prepared and screened for pancreatic lipase inhibitory activity [ 19 , 20 , 21 , 22 ]. Along with the conventional approaches, in silico models such as 3D QSAR, 2D pharmacophore, molecular docking, and molecular dynamics simulations are utilized to identify potential bioactive compounds for obesity treatment [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, orlistat remains the only PL inhibitor approved by FDA for obesity management in conjunction with a reduced caloric diet. However, orlistat can cause non‐negligible adverse effects, including stomach pain, steatorrhea and incontinence, abdominal cramping and fat‐soluble vitamin deficiencies, hepatotoxicity, and acute pancreatitis [16,17] . Thus, it is highly desirable to find more safe and effective PL inhibitors for the prevention and treatment of obesity.…”
Section: Methodsmentioning
confidence: 99%
“…Past research has demonstrated the importance of five‐membered nitrogen heterocycles on PL inhibitory profiles. For instance, oxadiazole (Point et al., 2012), 1,2,4‐triazole (Bekircan et al., 2014; Kahveci et al., 2017), triaza‐phospholinoalkanes (Hamzaoui et al., 2015), rhodanine (Chauhan et al., 2019), thiazolidinedione (Sridhar, Bhurta, et al., 2017) etc. have explored for PL inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the five‐membered heterocycles possessed these active warheads for the PL inhibition. For instance, thiazolidinedione and rhodanine analogues with a nitrogen centred diamide linkage exerted a potential PL inhibitory activity (Chauhan et al., 2019; George et al., 2020; Sridhar, Bhurta, et al., 2017). The structural diversity at two positions of thiazolidinedione and rhodanine offers an additional advantage for the further incorporation of essential pharmacophoric features coverts these as attractive structural scaffolds in the area of PL inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation